Social path assessment and food security status of rural households in Iran - Haghighi, Zahra; Namdar, Razieh (Frontiers in Sustainable Food Systems, 2024)
Introduction Food and nutrition are the most vital needs of human society and its provision lies in the category of food security. The concept of food security is very broad and is determined by the interaction of a range of biological, economic, social, agricultural, and physical factors. The purpose of this study is to investigate the social factors affecting food security among rural households. Methods This is quantitative research conducted by survey method. The statistical population included 384 rural households in Shiraz County that were selected by stratified random sampling. Data analysis was performed using SPSS and LISREL software. Results and discussion Results indicated that the values of combined reliability calculated for all three variables studied were >0.7, which implies that research tools have good reliability and validity. The results of structural analysis of social capital and social health variables with food security using confirmatory factor analysis techniques and structural equations showed social capital variable affects food security directly and social health variable has an indirect effect. According to the value of fitness indicators obtained; it was found that the structural equation model of the research variables had a suitable and acceptable fit and the general structure of the research was approved. Hence, the components used in the research were able to estimate food security. Accordingly, by improving the level of social capital and social health, promotion of food security in communities, would be expected.